Konstitusionalisme Perlindungan Anak terhadap Film di layanan streaming - Muhammad Ruhly Kesuma Dinata; Ibrahim Fikma Edrisy (UNIB Press, 2021)
Technological developments in films today are easily obtained through computers, laptops and smartphones by accessing streaming services and can be watched by all people, both young and old, regardless of age. This study uses a normative legal approach. With the streaming service, anyone who wants to enjoy movies can only access them via a computer screen and connected to the Internet without registering. It is accessible without paying a penny. How are children protected against films on streaming services, and what are the inhibiting factors for protecting children against films on streaming services? The objectives of this article are how to protect children against films on streaming services and what are the inhibiting factors for protecting children against films on constitutionalism streaming services; this means the entire fundamental law, both written and unwritten, which governs the administration of state administration in a country. This study uses a normative legal approach, where the data source is obtained from library materials or secondary data, which consists of primary legal materials, including basic norms or rules. In contrast, secondary legal materials include books, research results, and expert opinions. The data obtained will be analyzed using a qualitative descriptive method. Keywords: Children; Film; Streaming.